2019
DOI: 10.1007/s10499-019-00423-0
|View full text |Cite
|
Sign up to set email alerts
|

Predicting uptake of aquaculture technologies among smallholder fish farmers in Kenya

Abstract: In Africa, many governments and development agencies have promoted aquaculture as a panacea for household food security, rural development, and poverty reduction. However, aquaculture production in the continent remains low despite significant investments in research and technology development. While numerous initiatives have been directed at technological innovation and transfer, their present scale of uptake is very slow and therefore inadequate to achieve transformational change envisaged in the 2030 Agenda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 51 publications
4
66
1
6
Order By: Relevance
“…Salt farmer participation in the extension had a positive and significant effect with p-value < 0.01 and marginal effect value of 0.2697, which means that the average probability of salt farmer to attend extension to decide on geoisolator implementation was 26.97 percent higher than that of farmers who did not attend the extension. This result is similar to study conducted by Beshir et al (2012) and Asmelash (2014) in Ethiopia, Dhraief et al (2018) in Tunisia, Kumar et al (2018) in aquaculture and Obiero et al (2019) in Kenya, Ahmed & Anang (2019) in Ghana that extension agents showed a significant effect on adoption level since the availability of information provided by extension agents is expected to stimulate adoption. The extension agent as a source of information related to geoisolator technology that has a strong influence on farmers' adoption decisions.…”
Section: Factors Affecting the Decision Of Salt Farmer To Adopt Geoissupporting
confidence: 91%
See 1 more Smart Citation
“…Salt farmer participation in the extension had a positive and significant effect with p-value < 0.01 and marginal effect value of 0.2697, which means that the average probability of salt farmer to attend extension to decide on geoisolator implementation was 26.97 percent higher than that of farmers who did not attend the extension. This result is similar to study conducted by Beshir et al (2012) and Asmelash (2014) in Ethiopia, Dhraief et al (2018) in Tunisia, Kumar et al (2018) in aquaculture and Obiero et al (2019) in Kenya, Ahmed & Anang (2019) in Ghana that extension agents showed a significant effect on adoption level since the availability of information provided by extension agents is expected to stimulate adoption. The extension agent as a source of information related to geoisolator technology that has a strong influence on farmers' adoption decisions.…”
Section: Factors Affecting the Decision Of Salt Farmer To Adopt Geoissupporting
confidence: 91%
“…This finding was consistent with the result of the study conducted by Uaiene et al (2009) in Mozambique and Hu et al (2019) in China. Also, Akudugu et al (2012) and Udimal et al (2017) in Ghana, Beshir et al (2012) and Challa & Tilahun (2014) in Ethiopia, Obiero et al (2019) in Kenya, that the larger production area owned by farmers, the more they will adopt modern technology. Furthermore, a contradictive thing from Israel mentioned by Yaron et al (1992), was a small land area tend to adopt technology with input-intensive innovation.…”
Section: Factors Affecting the Decision Of Salt Farmer To Adopt Geoismentioning
confidence: 99%
“…The findings concur with previous research about farmer knowledge on introduced agricultural technologies to influence uptake and extent of use of improved crop varieties [19,24,41,42]. Similarly, farmer attitude result resonates with findings by [67] in Kenya, showing farmer attitudes to be key indicators in predicting uptake of aquaculture technologies among smallholder fish farmers.…”
Section: Factors Associated With Intensity Of Farmer Uptake Of Tc Bansupporting
confidence: 87%
“…Pelatihan dan percontohan farming (demfarm) dengan pendekatan kelompok bisa memberi hasil yang lebih baik (Srinath et al 2000). Beberapa faktor yang memengaruhi pembudidaya dalam mengadopsi teknologi antara lain pendidikan, diversifikasi kegiatan on-farm, ukuran wadah budi daya, tingkat produksi, kehadiran dalam pelatihan penyuluhan, kemudahan pemahaman, dan kemudahan teknologi penanganan (Obiero et al 2019). Kegiatan ini bertujuan untuk memberikan wawasan, keterampilan, dan motivasi serta mengembangkan teknologi tepat guna dan menciptakan segmentasi usaha baru, yakni usaha pendederan ikan kerapu bagi Kelompok Seafarming di Pulau Pramuka dan Panggang, Kelurahan Pulau Panggang, Kepulauan Seribu dalam rangka menguatkan agrbisnis ikan kerapu sebagai komoditas unggulan daerah.…”
Section: Pendahuluanunclassified
“…Peserta pelatihan berharap pendampingan yang intensif pada saat mereka mencoba usaha pendederan hingga panen. Untuk memfasilitasi pembelajaran dan pemanfaatan teknologi dan praktik yang baik oleh para peserta, tampaknya berbagai materi penyuluhan dan komunikasi terkait pendederan ikan kerapu, termasuk poster, brosur informasi hard copy dalam bahasa yang sederhana, presentasi video singkat, dan fitur radio perlu diadakan sebagaimana yang dilakukan oleh Obiero et al (2019).…”
Section: Pelatihanunclassified